Analisis Yuridis Penerapan Keadilan Restoratif dalam Tindak Pidana Pencurian Ringan (Studi Putusan No.2/Pid.C/2025/PN.Kbu) - Putri, Melia Andani; Sugeng Dwiono (Universitas Medan Area, 2026)
This study aims to Investigate the application of restorative justice in minor theft cases as reflected in dicision Number 2/Pid.C/2025/PN.Kbu with emphasis on the legal basis and judicial reasoning underlying the court’s verdict. This research employs normative legal research using statutory and case approaches. Primary legal materials consist of court decisions and legislation, on the other hand secondary legal materials include relevant literature and scientific journals. The results indicate that the application of restorative justice in this case was realized through judicial consideration of the agreement reached between the defendant and the victim, admission of guilt, and commitment not to reoffend. The judge based the decision on statutory provisions governing adjudication based on restorative justice and also considered sociological aspects and the objectives of sentencing. The study concludes that the use restorative justice in minor theft cases can promote restoration, balance, and legal benefit without neglecting legal certainty